Construction of binary phase diagram of palm kernel oil based glucosides: article - Osman, Faizza Nur Atika; Kamalul Aripin, Nurul Fadhilah (2017)
The glucosides with an average alkyl chain length of 14 carbon atoms derived from fatty acid of palm kernel oil have been synthesized and their phase behavior has been studied. The objectives of this study is to prepare a series of glucosides sample in water with different concentrations and to construct the binary phase diagram from palm kernel oil based glucosides .The scope of study is to study the formation of lyotropic phases at different concentration and temperature. The phase diagram is a best way to show formation of different phases with a given temperature and construct a phase diagram and know how to use it to predict behavior of materials which is glucosides. These phase diagrams provides boundaries of different phases. The binary phase diagrams of glucosides are constructed using cross polarizer films and optical polarizing microscopy (OPM).